A STUDY OF STUDENTS’ PERCEPTION TOWARDS THE CORRECTIVE FEEDBACKS USED BY THE TEACHER IN CORRECTING THE STUDENTS’ WRITING PROBLEMS - Asis Warni (Ensiklopedia Education Review, 2021)
This research aimed to find out the  students’ perception towards the corrective feedbacks used by the teacher in correctinng the students’ writing problems. The reseach employed descriptive method. The sample of this research  was selected by using random sampling technique. The instruments of data collection was a students’ checklist. The data of the students’ perception  towards  the  corrective  feedback stated that 59,09%  students  said  that  direct corrective  feedback help them to understand what to do to correct their errors. Next, the result shown that 54,55% of the students also mentioned that they can notice and understand their errors about   punctuation,   spelling,   and   capitalization   through   indirect   corrective feedback easily. Furthermore,  half of them or 50% of the sample students told that indirect corrective feedback encouraged them to write in a better topic and details. In conclusion, the corrective feedbacks improve student’s ability in writing especially descriptive text and the students have positive perceptions about the corrective feedbacks. Keywords: Perception, Corrective Feedback, Writing